PELATIHAN ENTREPRENEURSHIP MOTIVATION DALAM MEMBANGUN MENTAL ENTREPRENEURSHIP BAGI UMKM DI MASA PANDEMI COVID 19 - Huda, Nurul; Haryanti, Sri Chusri; Rini, Nova; -, Rosmelani (DEVOSI, 2021)
Micro, Small and Medium Enterprises in Indonesia are experiencing a negative impact from the COVID-19 pandemic. Thus, Micro, Small, and Medium Enterprises actors need an increase in entrepreneurship motivation to survive during the COVID-19 pandemic. The YARSI University Community Service Team and partners from Micro, Small and Medium Enterprises who are members of the YARSI University with the Warung Sejahtera Business Group conducted training on entrepreneurship motivation. The activity results show that there are still Micro, Small and Medium Enterprises actors who do not know about the COVID-19 pandemic and entrepreneurship motivation. After participating in the training, most MSME actors are interested in running a Micro, Small and Medium Enterprise business during the COVID-19 pandemic by innovating. The innovation that Micro, Small and Medium Enterprises will carry out is the most widely chosen by sharing info to the WA group. This community service activity concludes that there is an increase in Micro, Small and Medium Enterprises' entrepreneurship motivation to stay afloat during the covid 19 pandemic. Future community service activities can be in the form of training on the operationalization of the WhatsApp application in increasing sales of Micro, Small and Medium Enterprises.